2011
DOI: 10.1124/jpet.111.184762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorpyrifos and Chlorpyrifos-Oxon on the Dynamics and Movement of Mitochondria in Rat Cortical Neurons

Abstract: Organophosphate (OP)-based pesticides have been used extensively for decades, and as a result, they have become almost ubiquitous in our environment. There is clinical and animal evidence to suggest that chronic exposures to OPs can lead to cognitive dysfunction and other neurological abnormalities, although the mechanism for these effects is unknown. We previously reported that repeated, subthreshold exposures (defined as doses not associated with signs of acute toxicity) to the commonly used OP chlorpyrifos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 35 publications
(32 reference statements)
3
44
1
Order By: Relevance
“…Monocrotophos have also been shown to induce apoptosis in neurons and inhibit metabolism 34. Chlorpyrifos and chlorpyrifos-oxon exposure resulted in increased mitochondrial length, decreased number of mitochondria and decreased mitochondria movement in axon at concentrations that did not inhibit AChE 36. Taken together, the evidence that OPs cause cell death specifically mediated through the disruption of mitochondrial functioning is not adequate and our results suggest that while a large number of OPs increased PD risk the mechanisms of action remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Monocrotophos have also been shown to induce apoptosis in neurons and inhibit metabolism 34. Chlorpyrifos and chlorpyrifos-oxon exposure resulted in increased mitochondrial length, decreased number of mitochondria and decreased mitochondria movement in axon at concentrations that did not inhibit AChE 36. Taken together, the evidence that OPs cause cell death specifically mediated through the disruption of mitochondrial functioning is not adequate and our results suggest that while a large number of OPs increased PD risk the mechanisms of action remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Since, there are limited data about the hepatotoxicity of OPs in humans, it is not certain whether changes in biochemical parameters indicate actual liver damage. (90)(91)(92)(93)(94), energy production (93,(95)(96)(97), and cell death (98)(99)(100). Several studies have found an association between mitochondrial dynamics and malathion-induced drop in mitochondrial ATP synthesis in rat liver (9) or quinalphos and acephate effects on liver succinic dehydrogenase (84,85,101) and ATPase activities (87) -all of them the key enzymes for oxidative phosphorylation.…”
Section: Biochemical Evidence Of Op Hepatotoxicitymentioning
confidence: 99%
“…Specifically, cortical neurons were coincubated (for 24 hours) with either atropine (50 mM) or mecamylamine (10 mM) and a representative concentration of DFP shown to impair axonal transport (10 nM) in the first set of experiments (see Results). The representative concentrations of atropine or mecamylamine were based on previous in vitro studies (Middlemore-Risher et al, 2011).…”
Section: Mecamylamine and Atropine Coincubation Experimentsmentioning
confidence: 99%